Needs Tokoh Akito Hayasaka dalam Film Yomei Ichinen no Boku ga, Yomei Hantoshi no Kimi to Deatta Hanashi - Eva Ananda; Tri Mulyani Wahyuningsih (Vocational College of Diponegoro University, 2026)
This study discusses the needs of the main character Akito Hayasaka in the Japanese film entitled Yomei Ichinen no Boku ga Yomei Hantoshi no Kimi to Deatta Hanashi. The purpose of this study is to describe the needs of Akito Hayasaka through a literary psychology approach using Henry Murray's needs theory. The method used in this study is a qualitative descriptive method. The data for this study are dialogues and scenes of Akito Hayasaka's character. Using the free listening technique, data were collected by watching the film, observing conversations between characters, and the speech acts of the main character. The note-taking technique is an advanced technique for recording data that will be used in the study. Then the data were processed, classified based on Henry Murray's needs theory, and conclusions were drawn. The results of the study show that Akito Hayasaka has 10 needs, namely abasement (feelings of inferiority), understanding (interpersonal interest), deference (admiring work), affiliation (making friends), defendance (defending oneself from criticism), nurturance (pleasing weak people), achievement (having life motivation), rejection (rejecting offers), dominance (influencing others), and counteraction (accepting reality).